2021
DOI: 10.1111/joor.13169
|View full text |Cite
|
Sign up to set email alerts
|

A new masticatory performance scale to integrate food biting, comminution and mixing ability in removable partial denture wearers

Abstract: Background:The existing masticatory performance (MP) tests cannot comprehensively evaluate objective masticatory function. Objectives:We aimed to examine the construct validity and responsiveness and determine the clinically minimum important difference (MID) and related factors of a newly developed MP scale to integrate food biting, comminution and mixing ability in patients with removable partial dentures (RPDs).Methods: Masticatory performance tests using gummy jelly, peanuts and colourchangeable gum were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
0
7
0
5
Order By: Relevance
“…Given that fragmenting food depends more on the bite force and dental status, whereas mixing food to form a bolus depends more on tongue and jaw movements, these aspects should be considered complementary and equally essential [35].…”
Section: Discussionmentioning
confidence: 99%
“…Given that fragmenting food depends more on the bite force and dental status, whereas mixing food to form a bolus depends more on tongue and jaw movements, these aspects should be considered complementary and equally essential [35].…”
Section: Discussionmentioning
confidence: 99%
“…También se lleva a cabo con diferentes alimentos artificiales como cubos de cera de dos colores o goma de mascar de dos colores, aunque en realidad en este caso lo que se evalúa es la capacidad de una persona de mezclar los alimentos. 13,22 Entre los alimentos artificiales más comúnmente utilizados se encuentran los cubos 23 o tabletas de silicona por condensación, 16 además del uso de formas diversas en jalea. 24 Al evaluar la capacidad de fractura se considera más conveniente utilizar alimentos naturales, ya que los pacientes conocen esos alimentos, los han consumido y tienen un sabor y textura conocida; sin embargo, la desventaja es que es más complicado estandarizar el alimento prueba y cualquier modificación en la dureza, tamaño o hasta la forma puede alterar los resultados.…”
Section: Wwwmedigraphicorgmxunclassified
“…Los alimentos prueba artificiales sí se pueden estandarizar, por lo que se considera conveniente emplearlos, además de que no son tóxicos y se le indica al paciente que no los degluta. La evaluación de esta capacidad de fractura se ha utilizado, entre otras situaciones, para evaluar qué tan afectada está la función masticatoria con la pérdida de los dientes posteriores o extensamente en el campo de las prótesis donde se determina la mejora de la función masticatoria después del uso de implantes o prótesis 22,25,26 y menos en otras áreas como la ortodoncia para determinar la disminución de la capacidad de fractura en pacientes con maloclusiones 27 o si un tratamiento de ortodoncia mejora el desempeño masticatorio. 28 Estos métodos se emplean en proyectos de investigación adecuadamente estructurados, pero la pregunta es, ¿realmente como odontólogos nos preocupamos por mantener y/o restaurar la función masticatoria del paciente?…”
Section: Wwwmedigraphicorgmxunclassified
“…The sieve method has long been used to measure MP; however, this method has significant limitations, in that the operation is complicated, and the analysis is lengthy. Therefore, many methods using impression material [1], color-changing gum [2,3], paraffin wax [4], fuchsin beads [5], and gummy jelly [2,3,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] have been reported. Of these, measuring the amount of glucose extraction (AGE) from chewing gummy jelly was the most advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of MP by measuring AGE from chewing gummy jelly is performed in healthy dentate adults [6,7,12,16,21], elderly adults [13,14,17,21], removable partial denture patients [2,3,10], re-movable complete denture patients [9,15,19], implant denture patients [10,11], mandibulectomy patients [20], and other groups. In addition, it has also been reported that AGE tends to decrease due to tooth loss [8,14], and increases after treatment [2,11,15] and with growth [18].…”
Section: Introductionmentioning
confidence: 99%